Clinical Guidelines for Acupotomy Treatment of Knee Osteoarthritis - Working Group of Acupotomy Medical Branch of China Association of Chinese Medicine; XIU Zhongbiao; CHEN Changxian; ZHANG Jianxin; LV Yanan; WEI Song; ZHOU Yu; WAN Quanqing; ZENG Weiquan; CHEN Guoqiang; HUANG Huirong; CAI Zhaolian; et al. (康复学报)
Knee osteoarthritis is a chronic degenerative disease characterised by degeneration of articular cartilage, secondary bone formation, subchondral bone sclerosis and synovial inflammation, it belongs to the category of "Xibi" in Chinese medicine. With the accelerated ageing of the global population, the incidence of knee osteoarthritis is on the rise, which could have negative effects on the quality of life of patients. Acupotomy treatment is a form of treatment of traditional Chinese medicine, and has significant advantages in the treatment of knee osteoarthritis. Acupotomy treatment is an effective in treating knee osteoarthritis, it is based on the theory of acupotomy medicine, it uses an acupotomy as a treatment tool, piercing the human body with a needle, and exe- rting the therapeutic effects of the acupotomy in the human body. The clinical diagnosis and treatment guidelines for knee osteoarthritis based on the evidence-based medicine concept and method have significant implication, in standardizing the diagnosis and treatment of knee osteoarthritis, and improve the therapeutic effect of acupotomy treatment for knee osteoarthritis. This guideline summarizes the diagnosis and acupotomy treatment process of knee osteoarthritis from the aspects of scope, definition terminology, diagnosis of traditional Chinese and Western medicine, grading and staging, acupotomy treatment, and adverse reactions and management, aiming to provide guidance and reference for diagnosis and treatment in clinical, teaching and scientific research. 1) Diagnosis: the 2 parts, Chinese medicine diagnosis and Western medicine diagnosis, including diagnostic criteria, grading criteria, staging criteria, and Chinese medicine identification and classification. 2) Acupotomy treatment: including indications for treatment, contraindications to treatment, treatment protocol, post-treatment precautions, frequency and duration of treatment, outcome indicators, safety of acupuncture treatment, common adverse reactions and management. The treatment plan specifies the principles of treatment, the operational steps, the selection of treatment points, other synergistic therapies and other aspects of the treatment techniques. Adverse reactions include common adverse reactions and special adverse reactions, common adverse reactions such as dizziness, broken needles, local haematoma formation and local skin infections, and special adverse reactions such as nerve damage, vascular damage and knee infections. This guideline is clinical problem-oriented through constructing clinical problems, developing literature screening and evidence grading, forming recommendations, inquiring expert opinions, and finally standardizes the diagnostic criteria for knee osteoarthritis and acupotomy treatment protocols, etc. It aims to provide guidance on acupotomy treatment for physicians in orthopaedic surgery, pain medicine, and rehabilitation at all levels and in all types of rehabilitation institutions, Chinese medicine hospitals or general hospitals, with better clinical applicability and validity, and can provide a reliable evidence reference for the practice of clinical decision-making in knee osteoarthritis.